1999
DOI: 10.1029/1999jb900087
|View full text |Cite
|
Sign up to set email alerts
|

Global‐scale analysis of the mantle Pds phases

Abstract: Abstract.A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
170
3
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 159 publications
(193 citation statements)
references
References 63 publications
(6 reference statements)
19
170
3
1
Order By: Relevance
“…model (Kennett and Engdahl, 1991) and repeated in the global study of Chevrot et al (1999). This suggests that the 410 and 660 km discontinuities beneath Kimberley occur very close to their namesake depth, i.e.…”
Section: Transition Zone Thickness and Wavespeedmentioning
confidence: 95%
See 4 more Smart Citations
“…model (Kennett and Engdahl, 1991) and repeated in the global study of Chevrot et al (1999). This suggests that the 410 and 660 km discontinuities beneath Kimberley occur very close to their namesake depth, i.e.…”
Section: Transition Zone Thickness and Wavespeedmentioning
confidence: 95%
“…In a global study, Chevrot et al (1999) found this time difference to vary between 41.8 and 48.7 s. This spread can be largely explained by lateral velocity variations in the upper mantle (that is, at depth < 400 km). They found that most of the observed times between 41.8 and 43.0 s are for stations located on Precambrian cratons.…”
Section: The 410 520 and 660 Km Discontinuitiesmentioning
confidence: 99%
See 3 more Smart Citations